A influência da finura e do teor de adições minerais na carbonatação do concreto - Venquiaruto, Simone Dornelles (2002)
This work aimed at to investigate concrete carbonation due to the amount and fineness variations in pozzolanic cementitious mixtures. The binary mixtures with fly ash, rice husk ash and silica fume were obtained substituting cement mass by 8% of silica fume, and 25% and 50% of fly ash and rice husk ash. For each percentage two mixtures proportions were molded with two distinct fineness. As a whole eleven mixtures with water/cementitious materials relationship 0.35,0.50 and 0.65 were accomplished, that afterwards were tested to axial compressive strength and carbonation. The experimental investigation in order to determine the carbonation coefficients, consisted of three phases: humid curing for seven days, specimens preconditioning and accelerated carbonation test. The carbonation tests were accomplished in automatized climatic chamber with constant ratio of 5% of CO2, 23 ± 1ºC temperature and 75 ± 1% relative humidity. The results were analyzed comparing the different mixtures with a reference one, without mineral additions. In general, the investigated mixtures presented higher carbonation coefficient compared to the reference concrete. In strength equality of 40 and 60 MPa the mixtures that presented better performance were those with 25% rice husk ash and BET fineness 23 m²/g (fineness 1 – coarser) and with 25% of fly ash and BET fineness 3,5 m2/g (fineness 1 – coarser). Therefore, concrete elaborated with these mixtures would have less than 40 mm carbonated depth in 100 years, lying in durable concrete zone, with resistant useful life to the carbonation effects. In general, for 40 and 60 MPa equality strength, it is not worthwhile the fineness and amount increase of none of the investigated mixtures. It is conclude that the utilization of different amount and fineness of mineral additions is carbonation-limited, in spite of the mineral additions improve substantially other concrete properties, as showed by the literature.